Comparison of the incidence of osteoradionecrosis with conventional radiotherapy and intensity‐modulated radiotherapy. Issue 11 (31st May 2016) - Maesschalck, Thibault De; Dulguerov, Nicolas; Caparrotti, Francesca; Scolozzi, Paolo; Picardi, Cristina; Mach, Nicolas; Koutsouvelis, Nikolaos; Dulguerov, Pavel
Abstract: Background: Modern techniques of radiotherapy are supposed to decrease the incidence of osteoradionecrosis of the mandible (ORNM). The purpose of this study was to compare the incidence of ORNM after intensity‐modulated radiotherapy (IMRT) in comparison to conventional 3D conformal radiotherapy techniques (conventional RT). Methods: We conducted a retrospective study of consecutive unselected patients treated in a single institution between 2002 and 2012. To minimize confounding effects, only patients with oropharyngeal carcinoma without surgery of the primary site were included. Results: The cohorts included 145 patients in the conventional RT group and 89 patients in the IMRT group. Total incidence rate of ORNM was similar for both groups with rates of 11% versus 10% ( n = 16 for conventional RT and n = 9 for IMRT; p = 1.0). Subanalysis revealed more ORNM in T4 classified lesions with IMRT ( p = .007). Analysis of different risk factors showed no statistically significant difference between ORNM and no‐ORNM patients. Conclusion: We found no reduction in ORNM with IMRT. © 2016 Wiley Periodicals, Inc. Head Neck 38 : 1708–1716, 2016